2018
DOI: 10.1149/2.0931811jes
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic Phases in Aluminum Alloys and Their Roles in Localized Corrosion

Abstract: The intermetallic phases in AA7075-T6, including the nm-scale precipitate MgZnCu and 10-μm size Mg 2 Si, S-phase, Al 7 Fe 2 Cu(Mn), and Al 15 (FeMn) 3 (SiCu) 2, were identified and evaluated with respect to chemical composition, structure, and relative nobility. Evaluation of each major intermetallic particle (IMP) after exposure of the alloy to electrolyte allowed assessment of their roles in the localized corrosion. Different corrosion scenarios, including dealloying, trenching, particle etching out/dissolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(124 citation statements)
references
References 43 publications
4
117
0
3
Order By: Relevance
“…The electrochemical behavior of constituent phases may change over time. In a recent study, Zhu et al studied the evolution of corrosion behavior of intermetallic phases in Al alloys over time [43]. At the early stages, the corrosion attack occurred in the form of de-alloying.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical behavior of constituent phases may change over time. In a recent study, Zhu et al studied the evolution of corrosion behavior of intermetallic phases in Al alloys over time [43]. At the early stages, the corrosion attack occurred in the form of de-alloying.…”
Section: Resultsmentioning
confidence: 99%
“…At the early stages, the corrosion attack occurred in the form of de-alloying. However, as the time progressed, the particles became nobler as a result of Al dissolution [43]. This particle ennoblement may accelerate the galvanic dissolution of the surrounding matrix.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is due to the seawater flow, which accelerates the corrosion process, causing detachment of the destroyed passive layer and the appearance of new "fresh" areas, where the oxygen diffuses and is the oxidising agent in the cathodic corrosion reaction. It is also observed that on both surfaces (Figure 3c and d), some particles remained (named as D and F), and according to EDS (Table 3), they correspond to cathodic rich in Fe [7], reported in the reference sample as α-Al(Fe,Mn,Cu)Si [35]; these intermetallic particles promoted the preferential dissolution of the aluminium matrix [40,41]. Figure 4 compares the φ corr fluctuations of AA6061-T6 specimens exposed for different periods of times (0, 5 and 30 days) under laminar flow conditions (Figure 4a) and without flow (Figure 4b).…”
Section: Surface Analysismentioning
confidence: 81%
“…On amphoteric alloys such as Al, there is concern for the initiation of alkaline corrosion as well (Aballe et al, 2001;Tran et al, 2016). Alkaline corrosion phenomena may be especially severe when constituent particles intersect the alloy surface to act as fast cathodic reaction sites, which will form local alkaline regions that aggravate amphoteric substrate dissolution (Aballe et al, 2001(Aballe et al, , 2003Huang and Frankel, 2007;Zhu et al, 2018;McMahon et al, in review). Thus, the barrier and galvanic properties of the MRP must be properly balanced to optimize performance for specific substrates, with particular attention to reducing the risk for exacerbation of degradation.…”
Section: Optimization and Effectivenessmentioning
confidence: 99%